The Clinical and MRI Effect of TNF-α Inhibitors in Spondyloarthritis Patients With Hip Involvement: A Real-World Observational Clinical Study - Zhang, Kui; Zheng, Yan; Han, Qing; Liu, Ying; Wang, Weitao; Ding, Jin; Wang, Yan; Zhang, Bei; Jia, Junfeng; Zheng, Minwen; Zheng, Zhaohui; Zhu, Ping (Frontiers in Immunology, 2021)
Objectives: Hip involvement is an important cause of disability and poor prognosis in patients with spondyloarthritis (SpA). Tumor necrosis factor (TNF)-α inhibitor treatment has been demonstrated to be effective in SpA patients with hip arthritis; however, quantitative assessment using magnetic resonance imaging (MRI) in long-term follow-up needs further application and observation. Methods: A total of 239 patients were involved in this study. Methotrexate and sulfasalazine were given as basic treatment. In total, 165 patients received TNF-α inhibitors plus basic treatment and 74 received basic treatment only, as controls. Clinical symptoms were assessed at baseline and at weeks 12, 24, and 52. MRI performances of hip arthritis, including bone marrow edema (BME) and synovitis, was quantitatively assessed using the Hip MRI Inflammation Scoring System (HIMRISS). Results: The clinical values of erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), BASDAI, Harris hip score, and ASDAS-ESR in both groups showed significant clinical remission at week 52 (p<0.001). However, the change in disease activity levels at week 52 in the control group was significantly worse than in the TNF-α inhibitor group. At week 52, MRI showed a significant remission trend in the TNF-α inhibitor group versus baseline, and total HIMRISS scores were significantly decreased (26.49±10.37 vs. 20.59±9.41, p<0.001); the control group only had slight improvement (p<0.05). Conclusions: TNF-α inhibitors could significantly improve clinical and MRI manifestations of hip involvement in patients with SpA. Quantitative MRI assessment combined with clinical assessment can be used to accurately evaluate the treatment effect of TNF-α in SpA patients with hip involvement to help guide targeted treatment.